DISPERSING AGENTS WASTEWATER QUALITY FROM LATEX GLOVES MANUFACTURING BY TREATMENT USING Al2(SO4)3 AND PAC COAGULANT - Wahyu Ratnaningsih; Cahya Widiyati (Politek ATK Yogyakarta Press, 2023)
Waste is a residual result of a process that cannot be reused. The rubber industry is one of the waste-producing industries that if not managed properly, will cause environmental pollution. One of the rubber industries is the latex glove industry, which uses raw materials in the form of latex and chemicals as dispersing agents. Dispersing agents that already expired cannot be reused, so they need to be processed before being discharged into the environment. One of the methods used for treating this wastewater is the coagulation-flocculation method. This research is aimed to conduct the treatment of dispersing agents wastewater from latex glove manufacturing by the coagulation-flocculation method using coagulants to reduce the level of turbidity and COD concentration. The concentrations of Al2(SO4)3 and PAC coagulants used were 1.33 g/L, 1.67 g/L, and 2 g/L, respectively, with rapid stirring at 120 rpm for 2 minutes. The flocculant concentration used was 0.33 g/L, with rapid stirring at 25 rpm for 15 minutes. The results showed that Al2(SO4)3 coagulant was better at reducing turbidity levels up to 97.86% and COD concentrations up to 90.24% in the dispersing agents wastewater. Based on this study, the recommended dose of Al2(SO4)3 coagulant is 1.67 g/L. At this dose, there was a decrease in turbidity levels from 816 NTU to 17.43 NTU and a decrease in COD levels from 328 mg/L to 32 mg/L.